Chemical oxidative synthesis and characterization of poly(o-phenylenediamine) doped with different acids - Melad, Omar (European Journal of Chemistry, 2016)
Poly o-phenylenediamine (PoPD) doped with different acids such as hydrochloric, sulfuric, formic, phosphoric and glacial acetic acids was synthesized by a chemical oxidative polymerization technique using potassium dichromate as oxidizing agent. The polymer products were characterized by FT-IR and UV-visible spectroscopy. The FT-IR spectra showed shift to lower wave number in case of PoPD-H2SO4 and PoPD-H3PO4, indicating that the doping degree of PoPD in H2SO4 and H3PO4 are the greatest. A successful doping of PoPD in H3PO4 was observed in UV-vis spectroscopy. The three steps decomposition observed from the thermogravimetric analysis (TGA). The second step loss related to the loss of the dopant is found to be higher in H3PO4 doped polymer. The electrical conductivity values of PoPD-H2SO4 and PoPD-H3PO4 are found to be the highest among the other acids.